2019
DOI: 10.13189/ujer.2019.071907
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Programmable Logic Controller Teaching Aids for Control System Module in Vocational College

Abstract: Teaching aids are important in the process of teaching and learning. The use of teaching aids in teaching and learning process is necessary for teachers to ensure the delivery of information related to the subjects taught is more visible and systematic, so it can be followed by students. This study aims to develop a programmable logic controller learning kit as a teaching aid to enhance the understanding of students in the control system module in a vocational college. This study implemented a quasi-experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Students who do simulations with the help of PLC teaching aid have better interest and achievement in learning competencies compared to those who do not use the teaching aids in their learning activities. In line with study Yahaya, Mustafa, & Ahad [29], found a positive effect on students using PLC teaching aids in their learning activities compared to students using conventional methods, they can be enthusiastic and want to learn the topic of PLC. Students are more focused and pay full attention when PLC teaching aids are exposed to the learning process.…”
Section: Literature Reviewsupporting
confidence: 70%
“…Students who do simulations with the help of PLC teaching aid have better interest and achievement in learning competencies compared to those who do not use the teaching aids in their learning activities. In line with study Yahaya, Mustafa, & Ahad [29], found a positive effect on students using PLC teaching aids in their learning activities compared to students using conventional methods, they can be enthusiastic and want to learn the topic of PLC. Students are more focused and pay full attention when PLC teaching aids are exposed to the learning process.…”
Section: Literature Reviewsupporting
confidence: 70%